EFFICIENCY IN THE PURCHASE OF FOOD AND BEVERAGES IN OPERATION OF STAR HOTELS IN BALI - I Putu Astawa; I Putu Mertha Astawa; Ni Putu Wiwiek Ary Susyarini (Jurnal Internasional Ilmu Pengetahuan Terapan bidang Pariwisata dan Events, 2017)
The research aims to calculate efficiency in the purchase of food and beverages in star hotels in Bali. Ten five stars hotels receiving award as the best hotel from Trivadvesor in 2016 are chosen as research sample. Data are collected through questionnaire given to purchasing department. Data are analyzed using descriptive statistical analysis and economical order quantity (EOQ) analysis. Research result indicates that the system and process for the purchase of food & beverage in stars hotels in Bali covered contract system for purchasing of perishable foods such as vegetables; daily or monthly system to give freedom to hotels to buy required goods; standing order was used to order certain types of foods supplied by certain supplier; and cash purchase was used to buy food or beverages in small amount. The purchasing process in the hotel uses contract system and the level of efficiency could be improved using EOQ in purchasing. The purchasing of budgeted food and beverages will facilitate the purchase operation; however, it will be better if it includes the existing economic approach calculation in order to increase hotel’s performance. The use of EOQ method could reduce storage cost at the hotels. In the future, hotels should put more attention on such cost as storage cost and cost of order.